Diagnosis Dan Tatalaksana Benign Prostatic Hyperplasia: Sebuah Studi Literatur - Sagita Novendi, Harie (Jurnal Syntax Fusion, 2022)
Benign Prostatic Hyperplasia (BPH) is a medical condition that is often found in men and its incidence is influenced by age. In autopsy studies, the histologic prevalence of BPH was 8% in the fourth decade of life, 50% in the sixth decade of life, and 80% in the ninth decade of life. In addition, Benign Prostatic Hyperplasia (BPH) is a disease that is progressive and causes a decrease in the quality of life in men. Therefore, knowledge about the diagnosis and good management of BPH needs to be understood by every clinician. The writing of this article focuses on discussing the diagnosis and management of BPH. The method used in writing this article is literature review relevant sources from various references include scientific journals, the latest clinical guides from IAUI, websites, and the latest and most trusted textbooks on the topic of Benign prostatic hyperplasia (BPH). Based on the literature search, the diagnosis of BPH was established based on anamnesis, physical examination, and appropriate supporting examinations. In the history it is important to explore the various complaints that are typical of BPH patients. BPH is a medical condition that is often found in men and its incidence is influenced by age. This disease is progressive and causes a significant reduction in quality of life. The diagnosis of BPH is based on anamnesis, physical examination, and appropriate investigations. Treatment options or management in BPH patients consist of conservative therapy (watchful waiting), medication, and surgery.